A single center retrospective study of daratumumab, pomalidomide, and dexamethasone as 2nd-line therapy in multiple myeloma. Issue 12 (15th October 2021) - Liu, Lawrence; Fiala, Mark; Gao, Feng; King, Justin; Goldsmith, Scott; Wildes, Tanya M.; Stockerl-Goldstein, Keith; Vij, Ravi; Schroeder, Mark A.
Abstract: Daratumumab, pomalidomide, and dexamethasone (DPd) is an FDA-approved 3rd or later line of therapy for myeloma. However, as there are limited published data on the efficacy of 2nd-line DPd, we conducted a retrospective analysis ( n  = 33). Herein, we report our center's data for 2nd-line DPd. Our patient population had a high amount of high risk cytogenetics (45.5%). The overall response rate (ORR) was 84.9% with a 1-year Progression Free Survival (PFS) of 37.7%. In standard risk myeloma ( n  = 18), the ORR was 88.9% and 1-year PFS was 61.1% (95% CI 42.3–88.3%). In high risk myeloma (45.5%, n  = 15), the ORR was 80% with a 1-year PFS of 7.3% (95% CI 1.1–47.9%). This suggests that the efficacy of 2nd-line DPd in myeloma with high risk cytogenetics should be further investigated.